Redo surgery for persistent hyperinsulinemic hypoglycemia of infancy in the age of laparoscopic pancreatectomy - Saud Alshanafey; Sarah Saud Almanea (Annals of Saudi Medicine)
BACKGROUND: Persistent hyperinsulinemic hypoglycemia of infancy (PHHI) is a rare disease but the most common cause of persistent neonatal hypoglycemia, often requiring early pancreatectomy. In cases of persistent/relapsed hypoglycemia, redo surgery may be necessary. OBJECTIVES: We report our experience with the redo of laparoscopic pancreatectomy at a tertiary healthcare center. DESIGN: Single-center, retrospective study SETTING: Tertiary health care center PATIENTS AND METHODS: We conducted a retrospective review of the patients who underwent redo laparoscopic pancreatectomy between March 2004 and April 2021. Demographic, clinical, and follow-up data were collected and analyzed. Descriptive data were generated. MAIN OUTCOME MEASURES: Feasibility and safety of the procedure. Success in controlling the PHHI. SAMPLE SIZE: 82 patients RESULTS: We managed 82 patients with PHHI by pancreatectomy, 11 of whom (6 boys and 5 girls) required redo procedures to control hypoglycemia, with 2 needing 2 redo procedures. The mean age during the redo procedure was 21 months. The redo procedures were performed at a mean duration of 15.5 months after the primary pancreatectomy. All patients exhibited the histologically diffuse type. The mean follow-up was 7 years. All cases were managed successfully after the redo procedures. Six patients were on medical treatment, 4 developed diabetes mellitus, and 1 became euglycemic). Two patients developed severe pancreatitis postoperatively, 1 required drainage of the infected collection and 1 developed thrombosis of the inferior vena cava, which was managed with anticoagulation medication. CONCLUSIONS: Redo laparoscopic pancreatectomy is feasible, safe, and effective option for managing persistent or recurrent hypoglycemia after primary pancreatectomy in diffuse PHHI. Sufficient experience with laparoscopic pancreatectomy is required for redo surgeries. LIMITATIONS: Retrospective design of the study may introduce bias.